THEORETICAL AND PRACTICAL ASPECTS OF DEVELOPMENT AND EVALUATION OF EDUCATORS’ DIGITAL COMPETENCE IN A MILITARISED EDUCATIONAL INSTITUTION - Spridzans, Martins; Dzerviniks, Janis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Educators’ digital competence development, particularly in the context of development and implementation and of interactive e-learning content to enhance learners’ cognitive processes continues to be one of the key priorities both in civil and military training contexts. The fast and continuous growth of digital technologies in enhancement of teaching and learning process, the ongoing urge to harness the potential of digital learning opportunities persistently trigger the need to update and continuously sustain professional competences of educators including their digital competence. In order to find the ways to enhance educators digital competence, determine the factors which influence the formation of digital competenceauthors of the article conduct research to summarize the theoretical foundations on the process digital competence formation and development, analyze the influencing factors of positive and negative influence on digital competence development in the context of militarized education institution.Based on research findings the authors discover that due to the lack of systematic digital competence development and appropriate evaluation mechanism the potential of digital learning is not fully used. Educators of militarised education institutions need to constantly update competence on development of interactive training materials, assessment of digital competence should be more reliable and rigorous. On the basis of the research the authors put forward suggestions on the ways to develop and evaluate educators’ digital competence in militarised education institution.